Lightest to Heavy UHECR nuclei in a Local Universe - Fargion Daniele (EPJ Web of Conferences)
UHECR are evalueted in the frame role of different nuclei composition. Most of the past and present models are considering proton or iron as their main currier. Some attention has been paid to the role of the UHECR light nuclei in recent years. We update here the lightest nuclei UHECR model, able to explain the nearest AGN or Star Burst sources with the few observed Hot Spot clustering in AUGER and TA array data. Any additional components of the heaviest nuclei with the highest energy, more bent and smeared, may also fit recent AUGER and TA homogeneous records at those energy edges.